Proceeding : International conference on bioscience and biotechnology (ICBB) 2011 Oktober 11 th - 12 th, 2011, Yogyakarta, Indonesia - Proceeding... (State Islamic University Sunan Kalijaga, 2011)
wt,2/ws.Vol.1.c.1-3